(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Life survives on food and Life extinguishes sans food. Food never assures immortality but enables life healthy and happy. This mysterious universe itself appears to be a mass of food both for animate and inanimate things; every component of the creation becoming food for some other constituent part of nature. Food exists in innumerable forms with astounding contents – explored and exploited – and its manifestation is simply stunning. This planet earth covered by two thirds of water and one third of land with opulence of life sustaining vegetation, is a perpetual and renewable source of food for all creatures. The oceanic wealth is readily consumable cafeteria of human need and greed, the prowess of plants, rivers and valleys cater to the rational and irrational utility of speaking mammal and other brained animals. Ironically, ‘there is enough in the nature for the needs of human but not up to his greed.’ Indian culture and civilization which laid extraordinary emphasis on growing food abundantly and sharing it in abundance has been subjected to the tests of time. Foreign rule converted the traditional plenty into a scorching scarcity leading to unending series of famines. Independent India ingrained the Directive Principles of State Policy in its Constitution to establish welfare state with equalitarian society. As Hobbes admitted, every man has a right to disobey if he is ordered to abstain from the use of food, air, medicine or any other things without which he cannot live. Institutionalised State control over food production and distribution is designed to prevent social unrest, and thus individual right to food is not emphasized. The roots of the modern concept of right to food can be traced to the compulsions of democratic politics and international law and politics rather than in domestic law.